Households Perceptions on Factors Affecting Resilience towards Natural Disasters in Indonesia - Viverita, Viverita; Kusumastuti, Ratih Dyah; Husodo, Zaäfri Ananto; Suardi, Lenny; Danarsari, Dwi Nastiti (The South East Asian Journal of Management, 2014)
Most areas in Indonesia are prone to natural disasters. Learning the lessons from the Aceh Tsunami in 2004, areas with high risks of natural disasters are in the process of preparing themselves for such an unexpected event, by increasing their resilience. The objective of this study is to shed more lights on factors affecting the resilience from two sources namely, existing literatures and the application of disaster management in four disaster-prone areas in Indonesia -Padang, Sleman, Cilacap, and Palu. To enrich our analysis, we collect data from the field to compare the preparedness and to get insights on people’s perceptions towards the factors of resilience in those areas.We employ IDI and FGD to identify the factors of resilience and the preparedness in the areas investigated. Thereafter, a preliminary survey is conducted to identify people’s perceptions towards the aspects of resilience in the areas. Results from the survey conducted to 800 households in Padang and Cilacap indicates that from the social aspect, community’s value cohesiveness is one of important factor affecting their resilience towards natural disaster. In addition, since almost 85 percent of their income was spending to fulfill their daily basic needs such as foods, clothing, and housing. Therefore, when disaster occurred, they heavily relied on the help of debt or selling some of their assets, as well as used cash in hand as emergency funds. In general, respondents in all sample cities are able to re-start their economic activities as soon as two weeks after the event of disaster. In addition, the survey found that most of respondents were aware that the government has programs to educate people on the disaster mitigation.